2001
DOI: 10.2174/1389203013381170
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cysteine Protease Activity by NO-donors

Abstract: Cysteine proteases represent a broad class of proteolytic enzymes widely distributed among living organisms. Although well known as typical lysosomal enzymes, cysteine proteases are actually recognized as multi-function enzymes, being involved in antigen processing and presentation, in membrane-bound protein cleavage, as well as in degradation of the cellular matrix and in processes of tissue remodeling. Very recently, it has been shown that the NO(-donor)-mediated chemical modification of the Cys catalytic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 98 publications
(167 reference statements)
2
42
0
1
Order By: Relevance
“…Each of these enzymes possess active site cysteines that are reactive and susceptible to covalent modification (31)(32)(33). In the caspase activity assay, 10 M Aldi-1 or Aldi-2 showed no inhibitory effect on caspase-6, whereas the caspase-6 specific inhibitor, LE22, completely abolished the activity of this protease (Fig.…”
Section: Inhibition By Aldi Compounds Is Specific To Aldehydementioning
confidence: 96%
“…Each of these enzymes possess active site cysteines that are reactive and susceptible to covalent modification (31)(32)(33). In the caspase activity assay, 10 M Aldi-1 or Aldi-2 showed no inhibitory effect on caspase-6, whereas the caspase-6 specific inhibitor, LE22, completely abolished the activity of this protease (Fig.…”
Section: Inhibition By Aldi Compounds Is Specific To Aldehydementioning
confidence: 96%
“…Exogenous nitric oxide and physiologically relevant NO donors, such as S-nitrosoglutathine, SIN-1, SNP, and GEA3162 significantly enhanced neutrophil apoptosis [44][45][46][47][48]. Interestingly, high levels of ROS or reactive nitrogen species (RNS) inhibit caspase activity, indicating that an alternative caspase-independent death pathway may be involved in ROS-induced cell death [49,50]. It was reported that oxidative stress can trigger endonuclease G-mediated DNA fragmentation in the absence of caspase activity, providing a possible caspase-independent death pathway mediating ROS-induced neutrophil death [51].…”
Section: Intracellular Mediators Of Neutrophil Apoptosismentioning
confidence: 99%
“…Consensus S-nitrosylation motifs have been postulated by Stamler et al (1997). These motifs have been suggested to contain hydrophilic residues adjacent to the specific cysteine either in the primary structure (Stamler et al, 1997) or brought together by three-dimensional (3D) conformations (Ascenzi et al, 2000(Ascenzi et al, , 2001. However, our previous studies, utilizing short peptide sequences, suggested that S-nitrosylation may be independent of the amino acids surrounding the cysteine residue.…”
Section: Introductionmentioning
confidence: 99%